Facile skin targeting of a thalidomide analog containing benzyl chloride moiety alleviates experimental psoriasis via the suppression of MAPK/NF-κB/AP-1 phosphorylation in keratinocytes. Issue 2 (August 2020) - Tang, Kai-Wei; Lin, Zih-Chan; Wang, Pei-Wen; Alalaiwe, Ahmed; Tseng, Chih-Hua; Fang, Jia-You
Highlights: A thalidomide derivative was assessed for its anti-inflammatory activity. The derivative suppressed cytokine expression to a greater degree than thalidomide. The derivative penetrated skin due to its feasible lipophilicity and small size. This compound regulated inflammation via inhibition of MAPKs/NF-κB/AP-1 signaling. Thalidomide analog has potential as a therapeutic agent against psoriasis. Abstract: Background: Thalidomide can be a TNF-α inhibitor for treating skin inflammation. This drug exhibits a strong toxicity that limits its application. Objective: We synthesized a thalidomide analog containing the benzyl chloride group (2-[1-(3-chlorobenzyl)-2, 6-dioxopiperidin-3-yl]isoindoline-1, 3-dione, CDI) to examine anti-inflammatory activity against psoriasis. Methods: The evaluation was conducted by the experimental platforms of in vitro TNF-α- or imiquimod (IMQ)-stimulated HaCaT cells and in vivo IMQ-induced psoriasiform plaque. Results: Using the in vitro keratinocyte model, we demonstrated a greater inhibition of IL-1β, IL-6, and IL-24 by CDI than by thalidomide. No significant cytotoxicity was observed at 100 μM. CDI delivered facilely into the skin with a cutaneous targeting ability 228-fold greater than thalidomide. CDI caused a negligible irritation on healthy mouse skin. We showed that topically applied CDI reduced IMQ-induced red scaly lesions, hyperplasia, microabscesses, and cytokine expression in the mouse model. The skin-barrier function measured by transepidermal water loss (TEWL) could be partially recovered from 50.6–36.3 g/m 2 /h by CDI. The mechanistic study showed that CDI suppressed cytokine production by inhibiting the phosphorylation of NF-κB and AP-1 via MAPK pathways. Conclusion: CDI would be beneficial for the development of a therapeutic agent against psoriasis.